Custom-made Tailoring System for SyazaAhmed - Ismail, Qurratu Amirah; Hasan Basari, Abd Samad (Applied Information Technology And Computer Science, 2026)
SyazaAhmed Enterprise, a custom tailoring business in Batu Pahat, Johor, recognizes the growing demand for personalized clothing and the need to integrate technology into tailoring processes. However, the current manual system leads to inefficiencies, including measurement inaccuracies, slow order processing, and poor data management, which hinder customer satisfaction and business growth. This study proposes a web-based Custom-Made Tailor’s System to streamline operations, enhance accuracy, and improve customer experience. Using structured methodologies and tools such as Visual Studio Code, XAMPP, and MySQL, the system features online measurement submissions, fabric selection, and integrated CRM for efficient order management and communication. Key findings show that the system significantly reduces measurement errors, improves order processing times, and facilitates personalized services. The implementation of this system is expected to enhance operational efficiency, boost customer satisfaction, and establish SyazaAhmed Enterprise as a competitive leader in the tailoring industry.